Analisis dan Penerapan Database Mongodb pada Aplikasi Manajemen Dokumen di PT. XYZ - Yulius; Susetyo, Yeremia Alfa (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
The development of NoSQL databases has become increasingly popular due to the need for diverse data storage systems that can accommodate varying attributes. MongoDB is one such NoSQL database that uses a document data model with JSON data types, allowing for storing data with diverse attributes. This study aims to analyze and implement MongoDB in a document management application at PT. XYZ uses the waterfall method. The discussion results include the application system architecture, the advantages of MongoDB such as its flexible schema and lack of downtime during schema changes, and its drawbacks such as limited web hosting support. The study also covers the implementation of MongoDB CRUD operations in the document management application and system testing using BlackBox Testing. Based on the research, it can be concluded that using MongoDB in the document management application at PT. XYZ provides an effective and efficient solution for managing documents.